Welcome on Board? Appointment Dynamics of Women as Directors - Eline Schoonjans; Hanna Hottenrott; Achim Buchwald (Journal of Business Ethics, 2023)
Abstract Increasing the participation of women in top-level corporate boards is high on the agenda of policy-makers. Yet, we know little about director appointment dynamics and the drivers and impediments of women appointments. This study builds on organizational and group-level behavior theories and empirically investigates how ex-ante board structures and gender-specific board dynamics impact the representation of women on corporate boards. We study boards of listed firms in Europe between 2002 and 2019 and find a declining appointment probability for every additional woman, i.e., the share of women already on the board negatively predicts the likelihood of additional women appointments. Further, we find evidence of a replacement effect, i.e., the likelihood of a woman being appointed as director is significantly larger when a woman, compared to when a man, leaves the board. We do not find spillover effects from non-executive to executive boards. These results are robust to econometric model specifications that address potential endogeneity concerns using matching and instrumental variables. Our results confirm that board director appointments are gender specific and suggest that demand-side factors such as explicit and implicit norms drive women appointments up to a certain threshold.
Additional information: G34;J08:J16;J71;L22
Keywords: 330; Executive directors; Non-executive directors; Appointments; Board dynamics; Gender; Tokenism; Critical mass; Corporate governance